A forward-looking Young Professionals Council (YPC). - Musingwini, C. (The Southern African Institute of Mining and Metallurgy., 2017)
Extract from Editorial: The holistic development of young professionals is critical for the future of our Institute and the industry. The SAIMM’s mentoring programme, which connects young professionals with experienced practitioners in a one-to-one mentoring relationship, is in its second year of existence. Our programme has matched 82 protégés to 64 mentors. This is a truly global programme because the registered participants are from different countries including the UK and USA. This programme allows young professionals to build connections and develop into future leaders of our mining industry.
President's Corner: A forward-looking Young Professionals Council (YPC).
President's Corner, Editorial.
Keywords: SAIMM; Southern African Institute of Mining and Metallurgy; Mining professionals; Graduate employment; Mentoring programme; Young Professionals Council